VARIATIONS OF THE FINE STRUCTURE CONSTANT IN THE DUST-DOMINATED ERA, THE RADIATION, THE COSMOLOGICAL CONSTANT AND TOLMAN-OPPENHEIMER-VOLKOFF EQUATION - SULAIMAN KARIM POHAN ( NIM : 20211030); Pembimbing : Dr. rer. nat. Bobby Eka Gunara, M.Si., AZRUL
In this thesis, we construct the equation of motion for Bekenstein-Sandvik- Barrow-Magueijo (BSBM) lagrangian. Firstly, we consider the Friedmann-Lemaitre- Robertson Walker (FLRW) metric. We calculate Christoffel symbols, Ricci tensor, and Ricci scalar. After that, we find the Friedmann equation. Finally, we analyzed the solution in the dust dominated era, the radiation dominated era, and the cosmological constant dominated era. Next, using the static spherically symmetric metric, derived Tolman Oppenheimer- Volkoff (TOV) equation for BSBM theory. From the calculation resulted the same form between ordinary TOV and TOV for BSBM theory. Then, from the equation we get interior and exterior solution for the star, relativistic and nonrelativistic cases.